Prevalence and factors associated with advance health directives in frail older inpatients. Issue 7 (31st May 2022) - O'Leary, James J.; Reid, Natasha; Hubbard, Ruth E.; Peel, Nancye M.
ABSTRACT: Background: Advance health directives (AHD) can be used to explore and document patient preferences for treatment and are therefore an important aspect of care planning. Aims: To investigate the prevalence and factors associated with AHD among older inpatients. Methods: This retrospective study included 6449 patients, aged ≥65 years referred for specialist geriatric consultation between 2007 and 2018 in Queensland, Australia. The interRAI‐Acute Care Comprehensive Geriatric Assessment tool was used to calculate a frailty index (FI), range 0–1, based on 52 possible deficits, and categorised into intervals of 0.1 for analysis. FI was also grouped according to previously reported cut points: fit (FI ≤0.25), moderately frail (FI >0.25–0.4), frail (FI >0.4–0.6) and severely frail (FI >0.6). Results: An AHD was present in 1032 (16.0%) of 6449 patients. Those with an AHD were significantly frailer than those without an AHD (mean FI 0.52 vs 0.45; P < 0.001). Higher frailty (odds ratio (OR): 1.34 (1.27–1.40)), older age (OR: 1.04 (1.03–1.05)), living in an institution (OR: 1.33 (1.01–1.73)) and recent hospitalisation (OR: 1.42 (1.23–1.62)) were significantly associated with higher prevalence of AHD. Prevalence of AHD increased over time, from 7.6% ( n = 66) in 2008 to 35.4% ( n = 99) in 2017. Conclusions: The presence of AHD is associated with sociodemographic factors, as well as higher frailty levels. Prevalence of AHD among inpatients has increased over the past decade but remains modest.